Association between vascular aging and cardiovascular-kidney-metabolic syndrome - Zeng, Shuyi; Cui, Henghua; Liao, Wang; Qiu, Shiyu; Wang, Zhengdong; Wu, Zijia; Liu, Ming; Chen, Lei (Frontiers in Endocrinology, 2025)
BackgroundThe concept of Cardiovascular-Kidney-Metabolic syndrome (CKM), an intricate interplay among metabolic risk factors, chronic kidney disease (CKD), and the cardiovascular system, was introduced by the American Heart Association (AHA). This indicates a markedly increased susceptibility to various organ dysfunctions and adverse cardiovascular events. In CKM management, reliable markers are critical. The purpose of this study was to investigate the relationship between ePWV and mortality and prognosis in patients with CKM.MethodsThis study included 14,372 participants from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. ePWV assessed vascular aging and arterial stiffness. The association between ePWV and CKM, as well as their risk of death, was analyzed using weighted logistic regression and Cox proportional hazards models. Bootstrap sampling was used to analyze the mediating effect of the Triglyceride-Glucose Index (TyG) between ePWV and CKM. The Stage 4 ePWV threshold was further validated using an independent retrospective cohort of 3,157 patients from the cardiology department of a tertiary hospital in southern China.ResultsThe RCS analysis demonstrated a nonlinear positive association between estimated pulse wave velocity (ePWV) and cardiovascular–kidney–metabolic syndrome (CKM) (P < 0.01). Subgroup analysis indicated that this association was strongest among young adults aged 20–40 years (P < 0.01), whereas no significant association was observed in elderly individuals over 75 years old (P = 0.791). Kaplan–Meier curves showed that individuals with higher ePWV had significantly worse survival than those with lower ePWV. Further mediation analysis revealed that the triglyceride–glucose (TyG) index mediated 25.23% of the association between ePWV and CKM. In the external validation cohort, the ePWV threshold corresponding to CKM Stage 4 was 8.52, which was consistent in direction and statistical significance with the NHANES-derived model.ConclusionElevated ePWV is nonlinearly associated with increased CKM risk, particularly among young adults. This finding provides insights into managing arterial stiffness and preventing CKM progression in individuals at high risk of early cardiovascular disease.